The ethanol extract of Edgeworthia gardneri (Wall.) Meisn attenuates macrophage foam cell formation and atherogenesis in ApoE−/− mice - Tang, Le; Kuang, Cuifang; Shan, Dan; Shi, Min; Li, Jiangsheng; Qiu, Liang; Yu, Jun (Frontiers in Cardiovascular Medicine, 2022)
Introduction Atherosclerotic cardiovascular disease is the leading cause of death worldwide. The Edgeworthia gardneri (Wall.) Meisn is a Tibetan medicine commonly used to prepare herbal tea to alleviate the local people's metabolic diseases. However, the anti-atherosclerotic effect of ethanol extract of the flower of E. gardneri (Wall.) Meisn (EEEG) and its underlying mechanism remain unknown. Methods EEEG was used to treat low-density lipoprotein (ox-LDL)-induced macrophages to detect macrophage foaminess, cholesterol binding and uptake, and lipid transport-related gene expression. eEEG treated ApoE−/− mice fed a high-fat diet for 16 weeks to detect atherosclerotic plaque area, macrophage infiltration, and liver and small intestine lipid transport-related gene expression. Results EEEG inhibited macrophage-derived foam cell formation induced by oxidized low-density lipoprotein (ox-LDL) by reducing CD36-mediated lipoprotein uptake. EEEG significantly alleviated atherosclerosis in ApoE−/− mice fed a high-fat diet for 16 weeks. EEEG treatment significantly decreased atherosclerotic plaque area, macrophage infiltration, and increased collagen content. Moreover, EEEG treatment significantly downregulated mRNA expression of hepatic Srb1 and intestinal Npc1l1 and increased expression of hepatic Cyp7a1. Conclusion Our study highlighted that EEEG played a role in attenuating atherosclerotic plaque formation by reducing macrophage foam cell formation.